TEACHING MATHEMATICS THROUGH QUIZIZZ GAMES TO IMPROVE HIGH SCHOOL MATH LEARNING OUTCOMES - Khabibullaev Sherozbek Khamidulla ugli; Alijonov Sirojiddin Husan ugli (American Journals, 2024)
This research paper explores the effectiveness of using Quizizz games as a teaching tool to enhance high school mathematics learning outcomes. The study investigates how Quizizz, an interactive and gamified online platform, can be utilized to engage students, promote active learning, and improve their understanding and retention of mathematical concepts. The research methodology involves a quantitative analysis of pre- and post-intervention assessments to evaluate the impact of incorporating Quizizz games into the math curriculum. The findings suggest that integrating Quizizz games into high school math instruction has the potential to significantly enhance learning outcomes and foster a positive.
Keywords: Quizizz, gamified learning, mathematics education, high school, learning outcomes, student engagement, active learning, student motivation, retention of knowledge, quasi-experimental research, intervention, control group, treatment group, data collection, pre- and post-assessments, student feedback surveys, data analysis.